Distracting communications in the operating theatre. - Sevdalis, N; Healey, A; Vincent, C (2007)
RATIONALE AND AIMS: Research suggests that there are problems of communication effectiveness in surgery. Here we describe the content, initiators and recipients of communications that intrude or interfere with individual surgical cases. We also consider the level at which the surgical team and its team members are distracted by these case-irrelevant communications (CICs). METHODS: Two psychologist observers sampled 48 general surgery procedures and they recorded the initiator and the recipient of CIC events, their content and the level of observable distraction that they caused. RESULTS: Irrelevant comments and queries (i.e. 'small-talk') accounted for half of the observed CICs. From the remaining CICs that we observed, most were related to the organization and administration of the case-list, to operating theatre provisions and to teaching junior staff. Surgeons initiated a third of the observed CICs, while receiving two thirds of them. External staff visiting the operating theatre initiated the most distracting communications. The CICs addressed to surgeons introduced significantly less distraction to the operating theatre than those addressed to anaesthetists and nurses. CONCLUSIONS: Some of the observed CICs contributed to the administration of the operating theatre case-list. Nonetheless, this communication can interfere with highly sensitive work. More effectively co-ordinated communication could reduce this interference. More research should assess the communication effectiveness and the impact of CICs on task performance in the operating theatre.